Effect of Age and Sex on the Physico-Chemical and Sensory Quality of Meat from Giriraja Birds - Kogilasan, D; Mandal, P K; Venugopal, S; Pal, U K; Kasthuri, S; Gawdaman, G (Journal of Meat Science, 2026)
The present study was envisaged to assess the effect of age and sex on the physico-chemical and sensory quality of meat from Giriraja birds reared up to 12 weeks of age at weekly interval. A total of 100-day-old Giriraja chicks were reared in the institution poultry farm up to 12 weeks of age as per standard management practices. Birds were divided in to two groups viz., male (47 birds) and female (53 birds) after completion of 6 weeks of age. Six birds each from male and female groups were slaughtered every week from 8 to 12 weeks as per the standard procedures and meat samples were collected from breast and thighs for meat quality and sensory analysis. In male Giriraja birds highly significant (P<0.01) difference in the moisture content, significant (P<0.05) difference in pH, water holding capacity and fat content of meat were observed. Whereas, in female Giriraja birds significant difference (P<0.05) was noticed in the pH and fat content, no such significant (P>0.05) difference was found in the water holding capacity and protein content of meat at different weeks of age. Meat from Giriraja birds (male & female) of 8 weeks of age had higher moisture and less fat but no difference in protein content and the meat had comparatively higher level of acceptability. No significant (P>0.05) differences were noticed among the sensory attributes of meat from Giriraja (male& female) birds belonging to different weeks of age. However, meat from 9 weeks in male and 8 weeks in female had slightly higher acceptability scores for all sensory attributes when compared to that of other age groups. From this it was concluded that age of Giriraja bird has remarkable effect on the physico chemical and sensory quality of meat.